Antibiotics Alter Pocillopora Coral-Symbiodiniaceae-Bacteria Interactions and Cause Microbial Dysbiosis During Heat Stress - Connelly, Michael T.; McRae, Crystal J.; Liu, Pi-Jen; Martin, Cecily E.; Traylor-Knowles, Nikki (Frontiers in Marine Science, 2022)
Symbioses between eukaryotes and their associated microbial communities are fundamental processes that affect organisms’ ecology and evolution. A unique example of this is reef-building corals that maintain symbiotic associations with dinoflagellate algae (Symbiodiniaceae) and bacteria that affect coral health through various mechanisms. However, little is understood about how coral-associated bacteria communities affect holobiont heat tolerance. In this study, we investigated these interactions in four Pocillopora coral colonies belonging to three cryptic species by subjecting fragments to treatments with antibiotics intended to suppress the normal bacteria community, followed by acute heat stress. Separate treatments with only antibiotics or heat stress were conducted to compare the effects of individual stressors on holobiont transcriptome responses and microbiome shifts. Across all Pocillopora species examined, combined antibiotics and heat stress treatment significantly altered coral-associated bacteria communities and caused major changes in both coral and Cladocopium algal symbiont gene expression. Individually, heat stress impaired Pocillopora protein translation and activated DNA repair processes, while antibiotics treatments caused downregulation of Pocillopora amino acid and inorganic ion transport and metabolism genes and Cladocopium photosynthesis genes. Combined antibiotics-heat stress treatments caused synergistic effects on Pocillopora and Cladocopium gene expression including enhanced expression of oxidative stress response genes, programed cell death pathways and proteolytic enzymes that indicate an exacerbated response to heat stress following bacteria community suppression. Collectively, these results provide further evidence that corals and their Symbiodiniaceae and bacteria communities engage in highly coordinated metabolic interactions that are crucial for coral holobiont health, homeostasis, and heat tolerance.